Multiparametric Oncologic Hybrid Imaging: Machine Learning Challenges and Opportunities - Küstner, Thomas; Hepp, Tobias; Seith, Ferdinand (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Background Machine learning (ML) is considered an important technology for future data analysis in health care.Methods The inherently technology-driven fields of diagnostic radiology and nuclear medicine will both benefit from ML in terms of image acquisition and reconstruction. Within the next few years, this will lead to accelerated image acquisition, improved image quality, a reduction of motion artifacts and – for PET imaging – reduced radiation exposure and new approaches for attenuation correction. Furthermore, ML has the potential to support decision making by a combined analysis of data derived from different modalities, especially in oncology. In this context, we see great potential for ML in multiparametric hybrid imaging and the development of imaging biomarkers.Results and Conclusion In this review, we will describe the basics of ML, present approaches in hybrid imaging of MRI, CT, and PET, and discuss the specific challenges associated with it and the steps ahead to make ML a diagnostic and clinical tool in the future.Key Points: Citation Format
Keywords: machine learning; hybrid imaging; multiparametric imaging